2020
DOI: 10.14202/vetworld.2020.1594-1598
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of androgen receptor and protein kinase A in male chicken following the administration of a combination of the epididymis and testicular extracts

Abstract: Background and Aim: Testis (T) and epididymis (E) are waste from the abattoir that is rarely used. In fact, both organs contain important chemicals needed for spermatogenesis (e.g., hormones, proteins, and other molecules). Therefore, administration of a combination of testis and epididymis (CTE) extracts may activate androgen receptors (AR) and protein kinase A (PKA) molecules that play a prominent role in spermatogenesis. We, therefore, aimed at investigating the influence of the CTE extracts on the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The previous study showed that administration of epididymis extract which in rich concentration of PACAP have potency in the increase of T concentration [43], FSH, LH, and follicle stimulating hormone-receptor expression [44], estrogen [45], dihydrotestosterone [46] and capable to increase the quality of spermatozoa in male local goat [47]. Furthermore, the study in male chicken showed that administration of epididymis and testicular extract combination influence the concentration of androgen receptor, protein kinase A [48], PACAP, protamine 1 and increase significantly the concentration of T [49].…”
Section: The Role Of Pacapmentioning
confidence: 99%
“…The previous study showed that administration of epididymis extract which in rich concentration of PACAP have potency in the increase of T concentration [43], FSH, LH, and follicle stimulating hormone-receptor expression [44], estrogen [45], dihydrotestosterone [46] and capable to increase the quality of spermatozoa in male local goat [47]. Furthermore, the study in male chicken showed that administration of epididymis and testicular extract combination influence the concentration of androgen receptor, protein kinase A [48], PACAP, protamine 1 and increase significantly the concentration of T [49].…”
Section: The Role Of Pacapmentioning
confidence: 99%